Case report: Low dose dexmedetomidine infusion for the management of hypoglycemia in a dog with an insulinoma - Green, Randolph; Musulin, Sarah E.; Baja, Alexie Jade; Hansen, Bernie D. (Frontiers in Veterinary Science, 2023)
Abstract Objective: To describe the use of a low dose dexmedetomidine constant rate infusion as preoperative treatment for hypoglycemia secondary to a functional pancreatic tumor in a dog. Case Summary: An 8.7-year-old castrated male Hungarian Vizsla, presented for further evaluation of persistent hypoglycemia after the referring veterinarian established a tentative diagnosis of insulinoma based on paired insulin and glucose measurements. Abdominal ultrasound and computed tomography demonstrated evidence of a pancreatic mass with possible hepatic metastases. Attempts to aspirate the lesions under ultrasound guidance were unsuccessful, and the dog was hospitalized overnight for planned surgical resection of the presumed pancreatic tumor and biopsy of the hepatic lesions the following day. In response to a progressive increase in patient anxiety and agitation, dexmedetomidine at a dose of 1 mcg/kg was administered intravenously immediately followed with a constant rate-infusion of dexmedetomidine at 1 mcg/kg/hr. The anxious behaviors were successfully controlled with minimal cardiovascular side effects. Serial blood glucose measurements obtained during this time demonstrated euglycemia. The dog remained euglycemic while receiving dexmedetomidine for the remainder of the pre-operative period and for duration of hospitalization following surgical resection and biopsy. New or Unique Information Provided: This case report demonstrates a possible role for alpha-2 agonist drugs to control and prevent hypoglycemia in dogs with insulinomas.